2020
DOI: 10.21315/tlsr2020.31.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterisation of Endophytic Bacteria from Coconut (Cocos nucifera) Tissue Culture

Abstract: Highlights • Five bacterial species were isolated and identified from coconut tissues. • Morphological, biochemical and molecular analyses revealed that four of the isolates were different strains of Bacillus subtillis. • The fifth isolate was identified as Pantoea dispersa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 32 publications
1
3
0
1
Order By: Relevance
“…Strain CTXW 7-6-2 was identified as a B. subtilis strain via morphological observation and combined analysis of 16S rRNA, gyrA, rpoB , and purH . Additionally, strain CTXW 7-6-2 produced a light-red pigment, which was consistent with an unknown B. subtilis strain isolated from coconut tissue culture ( Salo and Novero, 2020 ). Strain CTXW 7-6-2 inhibited pathogenic fungi associated with diseases that infect kiwifruit, tobacco, plums, and Chinese ground orchids, and adversely affected the hyphae of the pathogenic fungi B. dothidea , Phomopsis sp., and A. alternata , which cause soft rot.…”
Section: Discussionsupporting
confidence: 78%
“…Strain CTXW 7-6-2 was identified as a B. subtilis strain via morphological observation and combined analysis of 16S rRNA, gyrA, rpoB , and purH . Additionally, strain CTXW 7-6-2 produced a light-red pigment, which was consistent with an unknown B. subtilis strain isolated from coconut tissue culture ( Salo and Novero, 2020 ). Strain CTXW 7-6-2 inhibited pathogenic fungi associated with diseases that infect kiwifruit, tobacco, plums, and Chinese ground orchids, and adversely affected the hyphae of the pathogenic fungi B. dothidea , Phomopsis sp., and A. alternata , which cause soft rot.…”
Section: Discussionsupporting
confidence: 78%
“…Most of the soil isolates were also rod-shaped, gram-positive, catalase-producing, starch-hydrolyzing, oxidase and phosphate-producing isolates. These characteristics in this present study are not sufficient to identify the isolates to the genus level [ 53 ].…”
Section: Discussionmentioning
confidence: 91%
“…These isolates dominant from genus of Bacillus. Salo & Novero, (2020) reported that plants of same type or species have endophytic bacteria that are not always same. Research (Giyanto & Anwar Arifin, 2019) reported that isolates of endophytic bacteria isolated from cocoa plants could spur growth of cocoa plants.…”
Section: Root Length (Cm)mentioning
confidence: 99%